Essential of statistics for the behavioral sciences - Nolan, Susan A. (Worth Publishers, 2011)
Essentials of Statistics for the Behavioral Sciences by Susan Nolan and Thomas Heinzen is a concise, readable text that covers key statistical concepts. Exploring its wide variety of creative, step-by-step examples, students using Essentials will learn how to choose the appropriate statistical test, understand its conceptual significance, and calculate each statistic. With inviting examples using real-world data, the text teaches students to apply concepts and formulas to statistical questions that they will encounter in their academic lives and outside the classroom.